Numerical and experimental comparisons of pressed blades for large Francis turbine runners manufactured with a reconfigurable pressing setup and a conventional setup. (24th April 2019) - Champliaud, Henri; Feng, Zhengkun
Quebec hydraulic power plants are mainly operated with large Francis turbines due to their ability to comply with a wide range of rates of flow and falls' heights. The variation of hydraulic conditions from one site to another forced engineers to create each time a new design for the runners and consequently lead to different thicknesses, sizes and shapes for the blades. The unit production costs are inevitably high since the punch and die matrices are completely redesigned for the production of a specific batch of blades. In this paper, the authors focus on a reconfigurable setup of punch and die matrices for forming blades from very thick plates offering a flexible alternative to the conventional setup. First, in order to validate the numerical model, a finite element simulation of the pressing process with a continuous conventional punch and die pair is performed. Second, the methodology for setting up a reconfigurable punch and die pair, based on a dense distribution of spherical headed poles, is presented. The model is then inserted in the previous finite element procedure. Numerical results agree well with data collected on blades pressed for the rehabilitation of a hydropower plant in Quebec.